Critics to Metaphysics by Modern Philosophers: A Discourse on Human Beings in Reality - Fios, Frederikus (Bina Nusantara University, 2016)
We have entered the 21st century that is popularly known as the era of the development of modern science and technology. Philosophy provides naming for contemporary era as postmodern era. But do we suddenly come to this day and age? No! Because humans are homo viator, persona that does pilgrimage in history, space and time. Philosophy has expanded periodically in the long course of history. Since the days of classical antiquity, philosophy comes with a patterned metaphysical paradigm. This paradigm survives very long in the stage history of philosophy as maintained by many philosophers who hold fast to the philosophical-epistemic claim that philosophy should be (das sollen) metaphysical. Classical Greek philosopher, Aristotle was a philosopher who claims metaphysics as the initial philosophy. Then, Immanuel Kant, Hegel, Heidegger, Marx even Habermas offer appropriate shades of metaphysical philosophy versus spirit of the age. Modern philosophers offer a new paradigm in the way of doing philosophy. The new spirit of modern philosophers declared as if giving criticism on traditional western metaphysics (since Aristotle) that are considered irrelevant. This paper intends to show the argument between traditional metaphysical and modern philosophers who criticize metaphysics. The author will make a philosophical synthesis to obtain enlightenment to the position of human beings in the space of time. Using the method of Hegelian dialectic (thesis-antiteses-synthesis), this topic will be developed and assessed in accordance with the interests of this paper.